1999
DOI: 10.1038/sj.leu.2401582
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-Hodgkin’s lymphoma of bone: a clinicopathological investigation of 60 cases

Abstract: A retrospective analysis of patients presenting with primary lymphoma of bone (PLB) was performed to determine clinical factors affecting prognosis in relation to histological subtype and treatment outcome. Data from 106 patients, presenting with a PLB between 1943 and 1996, were retrieved from the files of the Netherlands Committee on Bone Tumours and Leiden University Medical Centre. The lymphomas were reclassified according to the REAL and updated Kiel classification. The clinical presentation, survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
121
2
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 17 publications
15
121
2
5
Order By: Relevance
“…The majority of these tumors are nonHodgkin's lymphomas, and as observed in our patient, as much as 92% are diffuse large B cell lymphomas (historically referred to as reticulum cell sarcomas) [6,14]. Peak age at presentation is during the fifth decade, with most occurring after skeletal maturity [18].…”
Section: Discussion and Treatmentsupporting
confidence: 54%
See 2 more Smart Citations
“…The majority of these tumors are nonHodgkin's lymphomas, and as observed in our patient, as much as 92% are diffuse large B cell lymphomas (historically referred to as reticulum cell sarcomas) [6,14]. Peak age at presentation is during the fifth decade, with most occurring after skeletal maturity [18].…”
Section: Discussion and Treatmentsupporting
confidence: 54%
“…Some series therefore have restricted the diagnosis to patients presenting with an isolated lesion of bone, although the most common site of spread is to additional osseous sites [6]. Furthermore, exclusion of patients with greater than Stage IE disease may confer the false connotation of a localized process to what is, in terms of staging, relapse, and patient survival, a systemic disease; the variable inclusion and exclusion of patients with distant sites of osseous or other systemic disease at presentation make analysis of the outcomes for the disease difficult.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically defined as "lymphoma presenting in an osseous site with no evidence of disease elsewhere for at least six months after diagnosis," it was first established as a clinical entity in 1939 (3). The majority of PNHLB have been more recently characterized as diffuse large B-cell lymphomas (DLBCL) using the REAL classification (4,5). Although many studies have reported the clinical, radiologic, and histopathologic parameters of PNHLB, few have addressed the molecular features to any significant extent (1, 4, 6 -10), likely because of their rarity and the paucity of tissue available in small biopsy specimens.…”
mentioning
confidence: 99%
“…Radiotherapy was established as the standard treatment in earlier years (19,20). However, with the development of highly effective chemotherapy regimens and particularly the advent of novel agents, such as the anti-CD20 monoclonal antibody rituximab, the role of radiotherapy has been increasingly questioned by certain researchers (2,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%